A narrative review of the role of psychological skills and characteristics in navigating the pathway to professional rugby union - McAuliffe, J.; Lavallee, D.; Campbell, M. J. (International Journal of Sport and Exercise Psychology, 2021)
To overcome the challenges associated with navigating the talent development pathway to professional rugby, players must possess certain psychological skills and characteristics (PSCs), e.g., motivation, confidence, and coping skills. It is essential to understand the PSCs that assist players in successfully transitioning through a talent development pathway and at the professional level, as that knowledge could be applied to enhancing psychological support. The goal of this narrative review was to synthesise research examining the PSCs that contribute to rugby players overcoming challenges to optimise their performance. To ensure objectivity within this review, a systematic approach was taken to the literature search and selection process of papers. Four databases were searched, and the key search terms used were "rugby" "psych*" "mental" and various combinations of these terms. From this process, ten relevant papers were identified. The review revealed that players need to possess a range of PSCs, notably motivation, commitment, coping skills, confidence, focus and self-regulation to navigate the talent development pathway in rugby successfully. It is suggested that players should be taught a wide range of psychological skills so they can develop the skills and characteristics to enable them to deal with the challenges they face and to optimise their performance. Future research should examine whether a training programme based on the PSCs identified would have positive effects on players navigating the talent development pathway to professional rugby.